PENGARUH KEPUASAN KERJA TERHADAP PRETASI KERJA DEGAN KOMITMEN KARYAWAN SEBAGAI VARIABEL MODERATINF PADA PT. SUKA FAJAR Ltd PEKANBARU - MITRA LINDA; Samsir Samsir; Dewita Suryati Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the PT. Suka Fajar Ltd located on Nangka street Pekanbaru. The company is engaged in sale and purchase vehicles either in cash or credit. The purpose of this research is to know the influence of job satisfaction and employee commitment to employee achievements and to determine the factors that influence employee achievements against the dominant in the PT. Suka Fajar Ltd. Pekanbaru. The population in this study were all employees who work at the company of PT. Suka Fajar Ltd. Selection of the population based on their termination of employment or reduction of other employees, while the samples is used by 55 people, in which the determination of the number of samples is done by using the formula Slovin. Hypothesis testing is done by the test F, t-test and the coefficient of determination (R2) Based on the results. we concluded that the job performance, employee satisfaction and employee commitment of PT. Suka Fajar Ltd, based on the respondents to the indictors of each variable is good, where the percentage of respondents to the ideal score is obtained by 66.97 (good), the percentage of the respondents to the indicators of job satisfaction of 65.88 (satisfied) and the percentage of respondents to the indicator of employee comitent obtainet at 69.21 (good). Partially (t-test) at the 95% confidence level there is a significant influence of the variable job satisfaction and employee commitment to employee performance, it is evident from the results of the test t. Simultaneously (F test) at the 95% confidence level, there is a significant influence of the variables of job satisfaction and employee commitment to employees as avidencet interpretation of the results of f. The relationship between job satisfaction and organizational commitment with employee performance can be said to be strong. it can be seen from the correlation coefficient. The contribution of the variable of job satisfaction and employee commitment to employee performance can be said to be high, it is reflected from the coefficient of determination.Keywords : Job Performance, job satisfaction, Employee Commitment,